Logic in earliest classical India - Gillon, Brendan S. (Motilal Banarsidass Publishers, 2010)
Papers presented at the 12th World Sanskrit Conference, held at Helsinki during 13-18 July 2003
Includes bibliographical references and index. - Includes passages in Sanskrit (roman); with English translation
Keywords: Aufsatzsammlung; Konferenzschrift; Logik; Pramāna; Indische Philosophie